2023
DOI: 10.3390/plants12040870
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol and Sorbitol-Mediated In Vitro Screening for Drought Stress as an Efficient and Rapid Tool to Reach the Tolerant Cucumis melo L. Genotypes

Abstract: An efficient method to instantly assess drought-tolerant plants after germination is using osmoregulation in tissue culture media. In this study, the responses of three Iranian melon genotypes to sorbitol (0.1, 0.2, and 0.4 M) or polyethylene glycol (PEG) (0.009, 0.012, and 0.015 M) were evaluated as drought stress simulators in MS medium. ‘Girke’ (GIR), ‘Ghobadloo’ (GHO), and ‘Toghermezi’ (TOG) were the genotypes. GIR is reputed as a drought-tolerant genotype in Iran. The PEG or sorbitol decreased the coleopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In vitro systems are rapid screening experiments that focus on quantitative features [24]. In addition, PEG can be used as an osmotic regulator in in vitro systems to simulate drought stress, as it reduces water potentiation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro systems are rapid screening experiments that focus on quantitative features [24]. In addition, PEG can be used as an osmotic regulator in in vitro systems to simulate drought stress, as it reduces water potentiation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Drought-induced enhancement of the ROS has previously been reported by Antonic et al [34] in Impatiens walleriana and Hajihashemi and Sofo [35] in Stevia rebaudiana, resulting in a significant decline in growth. Recently, in PEG-stressed Cucumis melo genotypes, Mehmandar et al [36] have demonstrated a significant enhancement in the H 2 O 2 and lipid peroxidation resulting in declined growth, biomass and yield production. Excess ROS affects membrane stability, electron transport, photosynthesis, protein cross-linking, protein synthesis, ion transport and enzyme activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of the activity of antioxidant enzymes due to PEG-induced drought stress has been reported in different crop plants including Triticum aestivum L [7], soyabean [45], Stevia rebaudiana [22] and Arachis hypogea [39]. Recently, it has been reported that the PEG-induced drought significantly up-regulates the activity of antioxidant enzymes, and plant genotypes exhibiting increased activities better tolerate the adverse growth conditions [36]. Increased functioning of antioxidant enzymes results in quick scavenging of toxic radicals, which reflects the protection of membranes, enzymes, proteins, lipids, nucleic acids, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the concentration of PEG, the more it inhibits the osmosis process within the cells, making it difficult for water to enter the cells. This condition mimics drought stress, hindering the growth of plant roots (Mehmandar et al, 2023).…”
Section: Root Initiation Time (Dap)mentioning
confidence: 99%